(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: One contributing factor of deaths due to uncontrolled hypertension is dietary disobedience because food affects blood pressure. Thus, Dietary Approach to Stop Hypertension for Indonesian (DASHI) is recommended, because it can control blood pressure in hypertensive patients. Objectives; This study aims to investigate the impact of DASHI diet adherence on systolic blood pressure (SBP) and diastolic blood pressure (DBP) changes in hypertensive patients. Material and Method: We performed a longitudinal study from May to September 2017 using primary data and non-random sampling method with purposive sampling. The data on blood pressure, food intake, physical activity, medication adherence, stress levels, smoking habits, routine blood pressure checks and routine weighting habits was collected via interviews, questionnaires and measurements. Result: For SBP, the first- and second-month average measurement in non-adherent respondents of the DASHI diet was 145.68 and 148.82 mmHg, respectively. Conversely, the third-month average measurement in obedient respondents was 137.88 mmHg. For DBP, the first-, second- and third-month average measurement in non-adherent respondents was 88.61, 87.84 and 84.48 mmHg, respectively. Conclusion: This study establishes a difference in SBP and DBP changes depending on the DASHI diet compliance based on the comparison of measurement results, including the first- and second-month measurement compared to third after controlling smoking and medication compliance covariates.